The value of restatement to fraud prediction - Qiu, Shi; He, Hong-Qu; Luo, Yuan-sheng (Journal of Business Economics and Management, 2019)
A financial report restatement reflects errors in the previous financial statement, and thus it increases investors’ doubt about the credibility of the financial statement. The primary objective of this paper is to examine whether restatement announcements imply increased fraud risks in Chinese firms in the context that up to one quarter of listed companies have restated their financial reports in China, and explore the implications of the content, severity and reasons for restatements with respect to fraud. In this paper, firms with financial restatements prove to be more likely to be labeled as fraudulent by regulators in China. Second, the following results also are revealed: (1) financial statements, except balance sheet restatements, provide insights into the revelation of fraudulent behaviors, (2) the severity of restatements is positively correlated with future fraud disclosures, and (3) restatements due to negligence are positively correlated with future fraud occurrences. These results imply that restatement announcements and their different characteristics provide important information for detecting financial statement fraud.